-2+4=-4g

Simple and best practice solution for -2+4=-4g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2+4=-4g equation:



-2+4=-4g
We move all terms to the left:
-2+4-(-4g)=0
We add all the numbers together, and all the variables
-(-4g)+2=0
We get rid of parentheses
4g+2=0
We move all terms containing g to the left, all other terms to the right
4g=-2
g=-2/4
g=-1/2

See similar equations:

| 2=-8w+5(w-2) | | 180=(6x+25)(2x+105) | | 2(-4n-7)=-18 | | -9+4x=6x-13 | | 4x=2=3x+4 | | -5(15x1)=2(7x-16)-x | | 120+62+x=180 | | -(9t-8)=-6-9t | | 9g=10g−5 | | V9k=5k-32 | | 9y-6=36 | | 3y+4=-6y-6 | | 105+9.5t=14.75t | | 3(h-9)+2h=h-27+4 | | 3(−5x−8)=8x | | 24p=774 | | -x-3=-2x+3 | | x-13+5x-13=149 | | 8u+10=9u | | 9.5t=14.75t+105 | | 32+2f=1 | | 13y-8y=2(5+15) | | -7/9u=-21 | | 5=5x10 | | 105+14.75t=9.5t | | x^2+4x-159=0 | | -10(n+3)=0.50(24-14n) | | |3m-9|=18 | | 42x+4+43x+1=180 | | 9x+9=11x-2x-9 | | 7/(m+8)=2/m | | (3x-5)=(7x+5) |

Equations solver categories